Analisis Karakteristik Serbuk Sabut Kelapa (Cocopeat) Sebagai Agregat Halus pada Campuran Beton - Hezliana Syahwanti; Irvhaneil Irvhaneil; Ranty Christiana (Jurnal Serambi Engineering, 2022)
The advantages of coconut coir powder (cocopeat) are resistant to microorganisms, weathering and resistant to mechanical spelling, namely friction and blows. Based on these advantages, cocopeat can be used as a blend of fine aggregates in the manufacture of concrete. The sieve test was conducted on the cocopeat to determine the initial feasibility analysis of cocopeat as a blend of fine aggregates in the concrete manufacturing. The results of the cocopeat sieve test are that cocopeat is included in Region II which is classified as a fine module of slightly coarse grains with a fine module of fine aggregate grains of 2.37. This shows that cocopeat has a fairly good value in normal concrete mixtures but is not suitable for high resistance concrete mixtures that exceed 25 MPa. This was followed by a subsidence test that gave subsidence values for mixtures of concrete with a cocopeat composition of 25%, 50% and 75%, is 7.5 cm; 5.3 cm; and 2.2 cm. While a good subsidence ratio is used in the range of 6-18 cm. In addition, the concrete with a 25% blend of cocopeat has a stronger physical form and there are no fungus growing on the surface of the concrete. Meanwhile, concrete with a mixture of 50% and 75% cocopeat looks more fragile and forms molds on the surface of the concrete. Thus the concrete with a mixture of 25% cocopeat has better results.